The Effect of Managerial Ownership, Firm Size, and Profitabilty to the Debt Policy of Indonesia Public Companies - Putra, Mohammad Rizky Fatoni (Jurnal Ilmiah Mahasiswa FEB, 2018)
The objectives of this study to test theoretically the influence of Managerial Ownership, Firm Size, and Profitability on Debt Policies of Indonesian Public Companies. This research uses explanatory research type. The research was conducted at a manufacturing company listed on Indonesia Stock Exchange (IDX) period 2014-2016. Sampling was done by saturated sampling method, and obtained 106 companies used as sample. This study uses secondary data sources. Data were analyzed using multiple linear regression model analysis. The results showed that managerial ownership had a significant negative effect on debt policy, firm size had a significant positive effect on debt policy, and profitability had a significant negative effect on debt policy.Â Keywords:managerial ownership, firm size, profitability, debt policy.